TEACHING SPOKEN DESCRIPTIVE BY USING CUE CARDS (ELang | An English Language Education Journal, 2019)
The research paper is entitled Teaching Spoken Descriptive by Using Cue Cards : A pre – experimental study done in the second grade of junior high school. This research was carried for implementing cue cards as the teaching media to improve students’ descriptive speaking skill in class VIII F of MTs Negeri 1 Bandung. This research was focused on: (1) finding out the effectiveness of using cue cards in teaching spoken descriptive . (2) finding out the students’ responses toward the use of cue cards in learning spoken descriptive. This research was implemented to 27 students (15 female and 12 male) registered in VIII F class. The pre-experimental design was employed in this research. Pre-test and Post-test as were applied the instruments. In the data analysis, the result of the pre-test and post-test was calculated by using Hatch & Farhady formula. Based on the result of the research indicated the progress of students’ teaching spoken descriptive by using cue cards. Students in this class were not good in speaking performances could be affected by the lack of other English skills. The students made a lot of mistakes in grammar and were lack of vocabulary mastery. As the derived t = ?1.347 does exceed the tabled critical value of t=2.056, at p=05 with df=26 (1.347 < 2.056). The result of the computation is lower than the tabled critical value. Therefore, Ho is retained. This means that there is no significant difference in the students’ score before and after the treatment using cue card. This also means that teaching spoken descriptive by using cue cards to the second grade of MTs Negeri 1 Bandung is not effective. Besides, the writer concludes from the questionnaires that all of students like in learning spoken descriptive by using cue cards. Students were interested in using cue cards and students speaking ability improved by using cue card media. It means the students response toward cue card media is good. So, the writer suggests that cue card is one of a good media for teaching learning process.